2002
DOI: 10.1111/j.1348-0421.2002.tb02764.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibody to Shiga Toxin 1, Which Blocks Receptor Binding and Neutralizes Cytotoxicity

Abstract: A monoclonal antibody, 5-5B, which neutralizes Shiga toxin 1 (Stx1) cytotoxicity of Escherichia coli, was constructed. An epitope analysis indicated that Asn55 in Stx1 B subunit was an important residue. This result and our previous results using an anti-Stx2 monoclonal antibody indicate that the region around the cysteine residue of the disulfide bond might be important for the neutralization of Stx cytotoxicity, making it a potential vaccination candidate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 8 publications
2
29
0
Order By: Relevance
“…The predominance of A-subunit-specific HuMAbs is consistent with previous findings in which the majority of murine Stx2-specific MAbs were also specific for the A subunit (6,25,28,29). Isolation of Stx2-specific human IgG1 and IgG3 HuMAbs with differential epitope specificity confirms previous findings that HuMAb___Mouse contains a sufficiently diverse repertoire of human heavy chain immunoglobulin loci capable of responding to a variety of antigens and undergoing isotype switching and affinity maturation (12).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The predominance of A-subunit-specific HuMAbs is consistent with previous findings in which the majority of murine Stx2-specific MAbs were also specific for the A subunit (6,25,28,29). Isolation of Stx2-specific human IgG1 and IgG3 HuMAbs with differential epitope specificity confirms previous findings that HuMAb___Mouse contains a sufficiently diverse repertoire of human heavy chain immunoglobulin loci capable of responding to a variety of antigens and undergoing isotype switching and affinity maturation (12).…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, passively administered Stx2e antiserum has been shown to prevent edema disease in swine (18). Several murine Stx2-specific monoclonal antibodies (MAbs) have been developed, and many have been shown to neutralize the activity of Stx2 in vitro and/or in vivo in mice (5,9,25,30,35). Here we describe development of a panel of Stx2 A-and B-subunit-specific human MAbs (HuMAbs), several of which similarly neutralize Stx2-mediated activity in vitro and in vivo.…”
mentioning
confidence: 99%
“…Prediction of conformational B-cell epitopes using Elipro was resulted to identify strong epitopes that can be used in immunodiagnostic tests and antibody production. The most probable Stx1A and Stx2A Stx1 A T290, I291, S292, S293 0.976 G25, T26, P27, L28, Q29, T30, I31, S32, S33, G34, G35, T36, S37, L39, M40, P211, D212, Y213, H214, G215, Q216, D217, S218, R220, G222, G227, S228, I229, N230, H245, A246, S247, R248, V249, A250, R251, M252, A253, S254, D255, E256, S259, P262, A263, D264, G265, R266, V267, R268, G269, I270, T271, H272, N273, K274, I275, L276, W277, S279, S280, T281, L282, G283, A284, I285, L286, M287, R288, R289 0.704 F7, S8, T9, A10, K11, T12, D15, G56, I57, D58, P59, E60, E61, G62, R63, F64, N65, N66, N83, R84, T85, N86, N87, V88, Y90, R91, F92, A93, S96, H97, V98, F100, P101, G102, T103, T104, A105, V106, T107, L108, S109, G110, V120, A121, G122, I123, S124, T126, G127, M128, Q129, I130, N131, H133, T136, T137, L140, D141, M143, S144, H145, S146, G147, T148, S149, L150, T151, Q152, S153, R179, T180, T181, D183, D184, L185, S186, G187, R188, S189, Y190, V191, M192 (Nakao et al 1999). Their findings indicated that three segments of 13C4 monoclonal antibody epitope are amino acids from 21-26, 45-52 and 74-81 with critical asparagine residue at position 55 that are necessary for binding of the 13C4 monoclonal antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The 13C4 MAb did not bind to StxB1 with the N55T mutation, nor did the antibody neutralize the Stx1 with the N55T mutation. The asparagine at the 55th residue of StxB1 is also a critical amino acid for the binding of another Stx1-neutralizing monoclonal antibody (5-5B) that recognizes the Stx1 B subunit but fails to recognize Stx1d (21). Additionally, a third MAb (2H3) that recognizes StxB1, but not StxB1d, has been described, and residue 55 may play a role in that difference as well (3).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a third MAb (2H3) that recognizes StxB1, but not StxB1d, has been described, and residue 55 may play a role in that difference as well (3). Finally, another MAb, VTm1.1 (later humanized and called TMA-15), recognizes StxB2 and neutralizes Stx2 (12,22) but fails to recognize StxB2 when the 56th amino acid is mutated (E56H). The 55th residue of StxB1 and the 56th residue of StxB2 are both located on the outside of the B monomers in approximately the same location.…”
Section: Discussionmentioning
confidence: 99%